2020
DOI: 10.1038/s41467-020-16896-0
|View full text |Cite|
|
Sign up to set email alerts
|

Evolution of generalist resistance to herbicide mixtures reveals a trade-off in resistance management

Abstract: Intense selection by pesticides and antibiotics has resulted in a global epidemic of evolved resistance. In agriculture and medicine, using mixtures of compounds from different classes is widely accepted as optimal resistance management. However, this strategy may promote the evolution of more generalist resistance mechanisms. Here we test this hypothesis at a national scale in an economically important agricultural weed: blackgrass (Alopecurus myosuroides), for which herbicide resistance is a major economic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
113
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 89 publications
(121 citation statements)
references
References 61 publications
(83 reference statements)
6
113
0
2
Order By: Relevance
“…Non-target-site resistance is a generalist resistance mechanism that develops independently from TSR, a specialist resistance mechanism that confers resistance to only one herbicide SoA, with several grasses exhibiting both classes of resistance ( Comont et al, 2020 ). EMR is one of the best-known mechanisms under-pinning NTSR and confers broad spectrum resistance to multiple herbicide SoA in weeds ( Ghanizadeh and Harrington, 2017 ; Gaines et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-target-site resistance is a generalist resistance mechanism that develops independently from TSR, a specialist resistance mechanism that confers resistance to only one herbicide SoA, with several grasses exhibiting both classes of resistance ( Comont et al, 2020 ). EMR is one of the best-known mechanisms under-pinning NTSR and confers broad spectrum resistance to multiple herbicide SoA in weeds ( Ghanizadeh and Harrington, 2017 ; Gaines et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…GSTs are known to detoxify herbicides through catalyzing their conjugation with glutathione (GSH) ( Cummins et al, 2013 ; Gaines et al, 2020 ). In Alopecurus myosuroides , the constitutive level of a glutathione transferase phi (F) class 1 protein ( AmGSTF1 ) was significantly higher in multiple herbicide resistance populations than in sensitive populations ( Comont et al, 2020 ). The biochemistry of AmGSTF1 and its transgenic expression in Arabidopsis thaliana showed that this protein has a functional role in regulating NTSR that extends beyond the glutathione conjugation of herbicides ( Cummins et al, 1999 , 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to multiple herbicides emerges as a challenge for current and future weed management. Chemical control practices that seek to reduce selection for specialist resistance traits may promote the evolution of generalist resistance ( Comont et al, 2020 ). The study of metabolic resistance mechanisms and the elucidation of a molecular basis is a difficult and arduous process but a better understanding of these generalist mechanisms will reinforce comprehension of the evolution of weed populations in response to selection pressures and contribute to the development of weed management strategies to delay resistance ( Nandula et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…AmGSTF1 levels in protein samples were quantified by ELISA using specific sheep antibodies raised against AmGSTF1 in 96well plates (Comont et al, 2020). Briefly, 96-well plates were coated with the primary antiserum (S909-D, diluted to 1 µg/ml in phosphate-buffered saline (PBS) for 16-18 h at 4 • C. Plates were washed four times with wash buffer [PBS with 0.1% (v/v) Tween 20 (Sigma Aldrich)] before black-grass protein (100 µg) extracts were applied.…”
Section: Enzyme-linked Immunosorbent Assay For Amgstf1mentioning
confidence: 99%